Association Between Human Leukocyte Antigen Class I and II Diversity and Non-virus-associated Solid Tumors - Liu, Zhiwei; Hildesheim, Allan (Frontiers in Genetics, 2021)
Homozygosity at human leukocyte antigen (HLA) loci might lead to reduced immunosurveillance and increased disease risk, including cancers caused by infection or of hematopoietic origin. To investigate the association between HLA zygosity and risk of non virus-associated solid tumors, we leveraged GWAS data from over 28,000 individuals of European ancestry who participated in studies of 12 cancer sites (bladder, brain, breast, colon, endometrial, kidney, lung, ovary, pancreas, prostate, skin, and testis). Information on HLA zygosity was obtained by imputation; individuals were classified as homozygotes at a given locus when imputed to carry the same 4-digit allele at that locus. We observed no evidence for an association between zygosity at six HLA loci and all cancers combined. Increase in number of homozygous at HLA class I loci, class II loci, or class I and II loci were also not associated with cancer overall (Ptrend=0.28), with adjusted odds ratios (ORs) for risk-per-locus of 1.00 (95% confidence intervals [CIs]=0.97, 1.03), 1.02 (0.99, 1.04), and 1.01 (0.99, 1.02), respectively. This study does not support a strong role for HLA zygosity on risk of non virus-associated solid tumors.